Molecular biodiversity of Iranian shallow water sponges. Issue 2 (17th February 2020) - Erpenbeck, Dirk; Gholami, Aref; Hesni, Majid Askari; Ranjbar, Mohammad Sharif; Galitz, Adrian; Eickhoff, Benjamin; Namuth, Leonard; Schumacher, Tatjana; Esmaeili, Hamid Reza; Wörheide, Gert; Teimori, Azad
Abstract : Despite their importance, our knowledge of the biodiversity and phylogeography of sponges in the Persian Gulf and adjacent waters is largely unexplored. Such knowledge, however, is necessary to better understand those patterns and processes that generated and maintained sponge diversity in this largely separated marginal sea, and to create a foundation for future exploration of the marine natural resources in this area. Recently, several expeditions resulted in the so far largest sponge collection of the Persian Gulf and Gulf of Oman, which now led towards the most comprehensive molecular taxonomic inventory of sponges in this region to date. We analyzed a total of 143 samples molecularly and identified 52 operational taxonomic units (OTUs) based on 28S and CO1. Additional molecular comparison with the Red Sea sponge fauna indicate a strong differentiation and high levels endemism between the Persian Gulf and the Red Sea respectively, supporting findings for other marine phyla.